(untitled) (Foro: Revista de Derecho, 2017)
La falta de una ley general de procedimientos administrativos ha hecho que, en el Ecuador, no exista una regulación clara sobre la forma de extinguir los actos administrativos. Ello ha generado prácticas administrativas que lindan con la arbitrariedad y no toman en cuenta los derechos generados en virtud de los actos de la administración. La reciente promulgación del Código Territorial soluciona en algo el problema, al establecer un procedimiento general para todos los gobiernos autónomos descentralizados. El presente texto analiza la forma en que el referido Código aborda el tema, forma que, si bien tiene sus particularidades, en general sigue el esquema del Estatuto del Régimen Jurídico y Administrativo de la Función Ejecutiva, permitiendo con ello una necesaria uniformización de procedimientos. The lack of a general law of administrative procedures has provoked that Ecuador does not have a clear regulation of the proceedings that must be followed to extinguish administrative acts. This situation produces administrative practices that border arbitrariness, as they do not consider the different rights that are generated as consequence of an administrative act. The recent issuance of the Territorial Code partially solves the problem, establishing a general procedure to be followed by all the decentralized autonomous governments. This article analyzes the regulations contained in the above mentioned Code, concluding that although it has its own particularities, in general, it follows the same scheme as the Statute of the Juridical and Administrative Regime of the Executive Branch, allowing, therefore, the necessary harmonization of procedures.